Experimental verification of acoustic communication along drill pipes - Lim, Eugene Shizheng. (2013)
Acoustic communications is a cost-effective to monitor real-time conditions of drilling operations. To predict the propagation behaviour of acoustic wave along drill pipes, the finite-different method is used. The results from the mathematical predictions were then verified with measurements taken from the scaled-down model of the drill string.